2010
DOI: 10.1111/j.1399-0012.2010.01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for children with Wilson disease: comparison of outcomes between children and adults

Abstract: LT is an excellent treatment option for patients with WD. Patients transplanted for CLD had higher patient survival rates than patients with FHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 27 publications
3
62
1
1
Order By: Relevance
“…Outcomes for graft and patient survival for WD are excellent for patients who undergo transplantation for acute liver failure or for liver failure from chronic liver disease. 12 Whether LT is indicated in patients with predominantly neurologic manifestations is controversial. This is due to the unpredictability of resolution of neurologic manifestations posttransplantation in LT recipients with neurologic manifestations and data suggesting that posttransplantation survival is worse in patients with neurologic involvement, as well as the scarcity of donor organs.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Outcomes for graft and patient survival for WD are excellent for patients who undergo transplantation for acute liver failure or for liver failure from chronic liver disease. 12 Whether LT is indicated in patients with predominantly neurologic manifestations is controversial. This is due to the unpredictability of resolution of neurologic manifestations posttransplantation in LT recipients with neurologic manifestations and data suggesting that posttransplantation survival is worse in patients with neurologic involvement, as well as the scarcity of donor organs.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…In a study analyzing UNOS results on 170 children and 400 adults who underwent liver transplantation for FW or end-stage liver disease in the United States between 1987 and 2008, Arnon et al [102] found that both one-and five-year survival rates were similar between children and adults (90.1% and 89% vs 88.3% and 86%, respectively, P = 0.53, 0.34). Moreover, both adults and children transplanted for chronic liver disease had better long term survival than patients transplanted for FW, although the difference was not statistically significant [107] . Neurological, and especially psychiatric [108] involvement may show little improvement with transplantation, however [27] .…”
Section: Liver Transplantationmentioning
confidence: 79%
“…74 In children, metabolic liver diseases are the second most common indication for liver transplantation after biliary atresia. Fifteen percent of children enrolled in the studies in the pediatric liver transplantation (SPLIT) registry underwent liver transplantation for metabolic diseases and 7.6% of them represented WD.…”
Section: Metabolic Liver Diseasesmentioning
confidence: 99%